Building and Urban Planning in Zimbabwe: Putting Needs, Costs and Sustainability in Focus - Chirisa, Innocent (Consilience, 2014)
This paper examines construction and its relationship with urban planning in Zimbabwe. Blame levelled against urban planning includes making the building process cumbersome hence raising of costs in the form of transaction costs. Planning and associated bureaucratic processes are often underestimated by most construction investors constitute the transactions costs. Although planning is critical for sustainability of the ultimate artefacts of buildings in Zimbabwe, it still relies heavily on the outdated standards set by the British in an environment (social, economic, and environmental) which has greatly changed. Issues relating to costs, investment, climate change, building materials and planning law are examined in as far as they shape, particularly, urban environments, which in essence must be sustainably built and meet relevant societal needs taking also on board, the question of technology. The paper is a theoretical and empirical review of the beneficiary needs and transaction costs (usually qualitative hence non-monetary, characterizing the construction projects. It examines both micro and macro-scale building processes and issues raised by different players in the industry.